Bimbingan Islam Dengan Pendekatan Tazkiyatun Nafs Untuk Meningkatkan Kesadaran Spiritual Warga Binaan Kurir Narkoba Dilapas Kelas II A Banyuwangi - Shoimah, Shinta Rohmatus; Yohandi; Sulaiman, A. Husam (Jurnal Ilmu Bimbingan dan Konseling, 2025)
This study aims to examine the implementation of Islamic guidance using the Tazkiyatun Nafs approach and its effect on increasing the spiritual awareness of drug couriers in Class II A Banyuwangi Prison. The research used qualitative methods with data collection through observation, interviews, and documentation of inmates and counselors who provided guidance. The results of the study show that Islamic guidance based on Tazkiyatun Nafs is effective in helping inmates realize their past mistakes, strengthen their relationship with Allah, and form better behavior and morals. This approach was carried out through self-reflection, understanding Islamic moral values, and strengthening spiritual discipline. In addition to increasing spiritual awareness, this guidance also had an impact on changing the social attitudes of inmates in the prison environment, supporting the process of social reintegration after release. Thus, the application of Tazkiyatun Nafs has proven to be a relevant guidance strategy for developing the spiritual and moral awareness of inmates.